Kinerja Pelayanan Petikemas Di Pelabuhan: Komparasi Pelabuhan Tanjung Perak Surabaya Dan Pelabuhan Di Asia - Dwi Cahaya Widiyono; Artiningsih Artiningsih (Universitas Islam Sultan Agung Semarang, 2020)
The focus of this paper is to evaluate the container services at Port of Tanjung Perak and compare it with other ports in Asia. A list of twenty (20) attributes is used as an assessment indicator with a five-point Likert scale, then analyzed using Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA) matrixes to measure service quality from users perspective. The results of the analysis addressed the CSI value of this study was 69.21% which refers to the service of the Port of Tanjung Perak Surabaya included in the category of satisfied. The IPA matrixes of the Port of Tanjung Perak confirm that three attributes were the main priorities for improved performance, namely related to congestion at the port, efficiency on-dock operation of containers at port and integration into intermodal transport system. In the ‘Assurance’ dimension, Port of Tanjung Perak is in the fourth position, above the Shanghai Port in China. In the ‘Tangible’, ‘Relability’, ‘Emphaty’ and ‘Responsiveness’ dimensions, Port of Tanjung Perak still needs to make continous improvements.